Defining Mental Health and Social Health for Public Health Practice in the United States Military - Kirsten M Anke; Matthew R Beymer; Esther J Pfau (Military Medicine, 2026)
Abstract: Clinically diagnosed mental health (MH) disorders accounted for the largest total number of hospital bed days and the second highest total number of medical encounters for U.S. Armed Forces active component members from 2019 to 2023. MH is largely influenced by social health (SH) outcomes and factors which include conditions at the relationship, command, and community levels for the military. While MH and SH definitions have been standardized for the civilian population, the unique aspects of the military environment call for military-focused MH and SH definitions. This commentary reviewed the existing civilian definitions on MH and SH and tailored these definitions to the U.S. military environment. By adopting standardized definitions for MH and SH in the military, public health practitioners can move towards developing surveys and interventions that holistically measure and address both MH and SH for service members and their dependents. MH and SH standardized definitions will allow for optimization of quality of life, which will further impact recruitment, retention, and military readiness.